Rancang Bangun Sistem Informasi Akademik Berbasis Web Pada Madrasah Ibtidaiyah Attaqwa 52 Bekasi - Hidayat, Mulia; Martini, Martini; Riana, Eri (Forum Kerjasama Pendidikan Tinggi, 2019)
Academic Information System at Attaqwa 52 Bekasi Madrasah Ibtidaiyah still done manually and the method is still less effective. So it is less fast and efficient in delivering information to teachers and students. Academic information system is a system designed to meet the needs of managing academic data such as student data, teacher data, scheduling and student grades. The development method used is the waterfall method, which is one of the methods of developing information systems that are systematic and quantitative, meaning that each stage in this method is carried out sequentially and continuously. With the availability of a system like this makes it easier for teachers and students to more quickly and easily see the class schedule and student grades